2020
DOI: 10.1103/physrevapplied.14.054019
|View full text |Cite
|
Sign up to set email alerts
|

Hard-Gap Spectroscopy in a Self-Defined MesoscopicInAs/AlNanowire Josephson Junction

Abstract: How to cite:Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…In order to demonstrate the feasibility and performance of our flip-chip approach, we investigated the coupling of the resonator to the device chip. Furthermore, we present single-tone as well as twotone spectroscopic measurements of an epitaxially grown InAs/Al half shell nanowire with a shadow mask defined Josephson junction [27,28]. We note that a similar flipchip method has recently been reported for Josephson junction detector based spectrometers [29].…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…In order to demonstrate the feasibility and performance of our flip-chip approach, we investigated the coupling of the resonator to the device chip. Furthermore, we present single-tone as well as twotone spectroscopic measurements of an epitaxially grown InAs/Al half shell nanowire with a shadow mask defined Josephson junction [27,28]. We note that a similar flipchip method has recently been reported for Josephson junction detector based spectrometers [29].…”
mentioning
confidence: 85%
“…The superconducting Nb resonator is connected to a directional coupler, thus providing the pump tone as the input signal and feeding the reflected signal back to the measurement setup. The mesoscopic nanowire Josephson junction is based on an epitaxial Al-InAs half-shell nanowire Josephson junction device that has been prepared by utilizing an in-situ shadow evaporation process [27]. In Fig.…”
Section: Flip-chip Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…However, recently it was demonstrated that closely separated superconducting electrodes can also be achieved by shadow evaporation technique, i.e. either by using a nanowire which crosses another [25][26][27] or using a patterned, suspended SiO 2 layer as a shadow or stencil mask. 18,22 All of these methods, have a common trait to potentially reach the so-called short channel limit, in which the current through the device is only carried by a single Andreev bound state.…”
Section: Introductionmentioning
confidence: 99%